Effect of Solution Concentration and Anodizing Coating Time on Hardness and Thickness Coating Of 7075-O Aluminum Alloy - Endramawan, Tito; Sifa, Agus; Suwandi, Dedi; Permana, Dudung Nana; Amat, Mohammad Azwar; Sukroni, Sukroni; Dionisius, Felix; Sukardi, Casiman (Jurnal Internasional Penelitian Teknologi Terapan, 2024)
One of the materials used in ship propellers is aluminum alloy. The advantages of aluminum are that it is easy to cast and relatively resistant to corrosion. This research aims to determine the effect of heat treatment and the effect of variations in the concentration of H2SO4 and immersion time in optimal of the anodizing process on the hardness value of 7075-O aluminum alloy (as-cast aluminum alloy). The method used is solution heat treatment at a temperature of 490ºC with a holding time of 6 hours, quenching using water or oil, with artificial aging at a temperature of 120ºC with a holding time of 24 hours. In the anodizing process, a sulfuric acid solution with various concentrations of 10%, 15%, and 20% with variations in immersion time of 10, 15, and 20 minutes. The results of vickers hardness test on heat-treated specimens with water quenching accompanied by artificial aging is 137.54 HV, it is increased by 47.44%. While the results of the vickers hardness test after anodizing is 213.09 HV, it is increased by 128.42%. Where the optimum hardness value was achieved at a concentration of 15% H2SO4 and an immersion time of 20 minutes. The coating thickness is equal to 25.79 µm.